The Effect Of Transformational, Transactional And Laissez Faire Leadership Styles Towards Employee Performance - Muhammad Hadi, Zamri (Universiti Malaysia Sarawak (UNIMAS), 2020)
This research aimed to investigate the effect of transformational, transactional and laissez faire leadership styles towards employee performance. Researches were mostly done in perspectives of quantitative methodology and the findings may differ between Western and Malaysian contexts. Quantitatively research and questionnaire were used as instrumentation for data collection. Pilot study was conducted by distributing 15 sets of questionnaires to determine the validity and reliability of questionnaire. Then the actual study was conducted at Tenaga Nasional Berhad Kota Baharu, Kelantan which involved 59 respondents. The data was analyzed by using Statistical Package for Social Science (SPSS) through descriptive statistic and Standard Beta Coefficient Analysis. The results of the study showed that transformational leadership style had the most significant relationship and the the most effect with employee performance. The findings of this research were beneficial for organization and future researchers. It is recommended that organization had to analyze their leadership styles and determine which leadership styles are more appropriate for managing the employee performance. Based on the findings, implication for future researcher are future discussed.